Marketing communication towards cruise ship passengers: the implications of market segmentation - Óskarsson, Gunnar; Georgsdóttir, Irena (Research in applied business and economics, 2017)
Tourism in Iceland has been growing incredibly fast during the past years; for example, the cruise industry has grown at a rapid rate, as Iceland continues to gain popularity as a cruise destination. Although a certain amount of research has been conducted in this sphere, it does not cover all of the important issues, including a better insight into clustering of cruise ship passengers, who differ from other tourists in a number of ways, and marketing communication towards them regarding product and services offered at the point of destination. The main objective of this research is to examine factors that have an impact on potential segmentation of cruise ship passengers coming to Iceland and learn about marketing communication practices used by local companies offering them products and services. Qualitative research was used as an approach and personal interviews chosen as a means of collecting information. Interviews were taken with 10 people from different companies who interact with cruise passengers on a regular basis at their workplace. The main findings reveal that participants note the strongest difference between cruise passengers of different nationalities, passengers coming on different ships (size and type), and passengers arriving at different times of the year. Concerning marketing communication towards cruise passengers, the results indicate that it is almost exclusively carried out through the Internet; a reliable website, search engine optimization and word-of-mouth. This research provides a contribution by deepening understanding of approaches that may be effective in market segmentation in this particular section of the tourism industry and identifying effective ways to reach potential customers. This research thus provides a significant addition to marketing knowledge for an increasingly important sector of the tourist industry.